Вплив бальнеотерапії на ріст лімфосаркоми Пліса - Івасівка, С.В.; Ковбаснюк, М.М.; Білас, В.Р.; Ходак, О.Л. (Медична гідрологія та реабілітація, 2004)
Установлено, что торможение роста перевивной лимфосаркомы Плиса под влиянием минеральной воды Нафтуся обусловлено формированием общей адаптационной реакции, которая запускается органическими веществами-ксенобиотиками этой воды. It is established, that the inhibition of the growth of the transplantative Plis' lymphosarcoma under the influence of the mineral water Naftussya is conditioned by formation of the common adaptative reaction, which is triggered off by organic substances-xenobiotics of this water.